The Role of Government in Indonesia’s Economy: State Budget, Fiscal, and Monetary Policies - Sifah Faoziah; Rifqi Rifqi (Penerbit Hellow Pustaka, 2025)
The government plays a strategic role in the national economy as a regulator, coordinator, and guarantor of public welfare. This role is manifested through regulatory functions, income redistribution, economic stabilization, the provision of economic stimulus, and protection for economic actors. In carrying out these roles, the government utilizes key policy instruments, namely the State Budget (APBN), fiscal policy, and monetary policy, which are interrelated and mutually reinforcing. The APBN serves as an instrument of planning, authorization, supervision, allocation, distribution, and economic stabilization, while also functioning as an essential tool for promoting economic growth and equitable development. Nevertheless, the management of the APBN continues to face challenges, particularly with regard to transparency and budget oversight, as reflected in cases of budget mismanagement that have resulted in state losses and hindered development efforts. Fiscal policy plays a crucial role in influencing macroeconomic conditions through the regulation of taxation, government expenditure, and deficit financing, implemented in the form of either expansionary or contractionary policies to maintain economic stability and fiscal sustainability. Meanwhile, monetary policy, implemented by the central bank, focuses on controlling the money supply, maintaining price stability, stabilizing the exchange rate, and safeguarding the financial system, while also taking into account global economic dynamics and developments in financial technology. From an Islamic economic perspective, monetary policy emphasizes principles of justice, equity, and the prohibition of riba (interest). The synergy between the APBN, fiscal policy, and monetary policy is essential in achieving stable, inclusive, and sustainable economic growth in Indonesia.